Adolescents’ health service utilization pattern and preferences: Consultation for reproductive health problems and mental stress are less likely - Berhane, Frehiwot; Berhane, Yemane; Fantahun, Mesganaw (The Ethiopian Journal of Health Development, 2016)
Abstract Background: Despite the growing health needs of adolescents due to intrinsic and extrinsic factors, health services in developing countries are not prepared to provide appropriate care due to inadequate awareness of adolescent health needs, and inadequate training and capacity of the service providers. Methods: A cross-sectional survey, to assess adolescents’ health service utilization pattern, their attitudes towards the existing health services and their preferences was conducted in selected schools in Addis Ababa using an anonymous self-administered questionnaire. Results: A total of 2,647 students from 13 high schools participated in the study. Of these, 1,177(44.5%) were males and 1,470(55.5%) were females. Considerable proportion of the adolescents reported that existing health services are inaccessible (30.5%), unaffordable (20.2%) and unacceptable (24.2%). The major barriers to utilizing reproductive health services are feeling of embarrassment (72.0%) and fear of being seen by parents or people who know them (67.8%). Adolescent’s preference regarding the service place and person serving varies widely; but the majority prefers special service hours designated for adolescents (70.1%), and a discounted price or free service (80.0%). Disclosing reproductive health problems and mental stress to parents, and seeking appropriate medical care for these problems is much less likely compared to other non-reproductive physical health problems. Conclusion: Adolescents are less likely to utilize existing health services when facing reproductive health problems and suffering from mental stress. Innovative and youth friendly approaches with due consideration of the heterogeneity of their needs should be adapted in order to increase accessibility and utilization of appropriate health services. [Ethiop.J.Health Dev. 2005;19(1):29-36]